Vacuum-free electric arc synthesis of titanium carbide using plant waste-derived carbon - Gumovskaya A. A. Arina Andreevna; Pak A. Ya. Aleksandr Yakovlevich; Yankovsky S. A. Stanislav Aleksandrovich; Nassyrbayev (Nasyrbaev) A. Artur; Nikitin D. S. Dmitry Sergeevich; Komkina U. S. Uljyana Sergeevna (2023, 2023)
Title screen